Variability and Heritability of Several Important Traits for Grape Production and Breeding - Radu E. SESTRAS (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2008)
Yield capacity, quality of grapes and resistance to downy mildew attack remain the important breeding objectives for grape. For these traits were analyzed more than 2200 F1 hybrids, belonging to eight combinations of wine grape. In each combination cv. Gewurztraminer was used, both as maternal and as paternal genitor, the other genitor being represented by an interspecific selection, rated as highly resistant to diseases (derived from Saint Emilion x Rayon d'or and Seyve-Villard 12-375 x Queen of Vine combinations). The rating of susceptibility to downy mildew in the tested hybrid individuals was performed in natural conditions of infection by visual observation and scored from "0"(no infection on leaves) to "5" (very severe infection), and the scale 1-5 was used for bunch number per hybrid and sugar content in grape must. Obvious differences for analysed traits were noted both among the studied combinations and within the same combination, depending on whether 'Gewurztraminer' has been used as maternal or as paternal genitor. These results suggest possible maternal effects on the phenotypic expression of these traits in grape vine. Variability indices (s%) were high and very high in all combinations (22.1-39.4% for response to Plasmopara viticola attack; 24.7-29.7% for bunch number per vine; 32.4-44.0% for sugar content in must, offering a good background for an efficient selection. The characters seem to be polygenically inherited, with high and very high heritability indices in the broad sense. The low values computed for heritability in the narrow sense suggest that except additive effects, epistasis and dominance effects have an important role in the phenotypic expression of vine yield capacity, sugar content of the must and resistance to downy mildew attack.